A stable Eu (III) coordination polymer for sensitive and selective sensing of Fe3+/Cr2O72− ions in aqueous medium. (1st January 2021) - Guo, Ruihong; Gao, Lingling; Zhou, Wendi; Zhang, Yujuan; Hu, Tuoping
Graphical abstract: A Pictogram: A 2D lanthanide coordination polymer [Eu(BCPB)(H2 O)2 ]n (1 ) solvothermally synthesized displays a red light emission, and has highly sensitive detection of Fe 3+ /Cr2 O7 2− ions in aqueous solution by a fluorescence quenching effect. Highlights: A 2D lanthanide coordination polymer (1 ) was solvothermally synthesized and characterized. 1 displays a red light emission and has highly sensitive detection of Fe 3+ /Cr2 O7 2− ions in aqueous solution. The quenching mechanisms of 1 Fe 3+ and Cr2 O7 2− for 1 were investigated in detail. Abstract: A lanthanide coordination polymer [Eu(BCPB)(H2 O)2 ]n (1 ) was synthesized based on a semirigid tripodal polycarboxylic acid ligand (H3 BCPB = 3, 5-bis(2-carboxy-phenoxy)-benzoic acid). Single crystal X-ray diffraction analyses showed that compound 1 exhibits 2D layer structures with [Eu6 (COO)22 (H2 O)12 ] SBU. Furthermore, fluorescence tests demonstrated that 1 has highly sensitive detection for Fe 3+ /Cr2 O7 2− ions in aqueous solution by a fluorescence quenching effect. Meanwhile, the quenching mechanisms of 1 for Fe 3+ and Cr2 O7 2− were also investigated in detail.